2007
DOI: 10.1210/jc.2007-0078
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Growth after Two Years of Growth Hormone Therapy in Very Young Children Born Small for Gestational Age and without Spontaneous Catch-Up Growth: Results of a Multicenter, Controlled, Randomized, Open Clinical Trial

Abstract: Very young SGA children without spontaneous catch-up growth could benefit from GH treatment because growth was accelerated and no negative side effects were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
21
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 21 publications
4
21
0
4
Order By: Relevance
“…In our patients, an increment of 1.3 SDS was observed in the height score during the 1st year, and an overall gain of 2.1 SDS was present after 2 years of rhGH treatment, which is similar to the values described in other studies including SGA patients born at term [24]. …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our patients, an increment of 1.3 SDS was observed in the height score during the 1st year, and an overall gain of 2.1 SDS was present after 2 years of rhGH treatment, which is similar to the values described in other studies including SGA patients born at term [24]. …”
Section: Discussionsupporting
confidence: 90%
“…As also reported by Argente et al [24] in term SGA infants, despite the high dose regimen employed, there was no abnormal acceleration of BA in preterm SGA patients included in this study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Some, but not all of those children, have a growth hormone (GH) deficiency [38, 39]. It has been shown that GH therapy increases the catch-up growth and, thereby, reduces the risk of short adult stature [40-42]. Further, there is some evidence that children born SGA who receive GH therapy have an improved cognitive development compared with their counterparts not receiving GH therapy [33].…”
Section: Discussionmentioning
confidence: 99%
“…4 Growth hormone therapy is effective to reduce risk of stunting among most SGA cases by improving height growth. 5 However, there is still debate on the best timing to initiate growth hormone therapy for SGA newborns because many of them will have postnatal "catch-up" growth spontaneously. 6 Therefore, to find SGA newborns with high risk of stunting by their etiology may inform earlier treatment and reduce stunting risk in later life.…”
mentioning
confidence: 99%